Karakteristik Fisik, Kimia, dan Daya Terima Kerupuk Karak dengan Penambahan Tepung Beras dan Tepung Tapioka serta Perbedaan Metode Pemasakan - Hapsari, Rahma; Supriyanto, Supriyanto; Triwitono, Priyanto (Pro Food, 2024)
The innovation of making karak crackers can be done by using the one-time cooking method and adding flour as a thickener. This method is more efficient than the usual two-times cooking method. And replace the use of bleng because it can affect the health of the body. The flour used is rice flour and tapioca flour. The purpose of the study was to examine the effect of the ratio of rice flour and tapioca flour addition and the method of making karak crackers on chemical, physical, and sensory properties. A two-factor completely randomized design was used to study the effect of the ratio of rice flour to tapioca flour (0:1; 1:1; 1:2; and 1:0) and the cooking method factor (two-time and one-time cooking method). Karak crackers were tested for chemical characteristics (moisture content and amylose content), physical characteristics (texture hardness, development volume, and brightness), and panelist’s acceptability. The results showed that the ratio of rice flour and tapioca flour in Karak crackers significantly affected amylose content, moisture content, texture hardness, and development volume). Meanwhile, the cooking method significantly influenced moisture content, development volume, and brightness. Panelist acceptability also showed that samples with rice flour and tapioca flour in the ratio of 0:1 and 1:1 in the factor of two-time cooking and samples with a ratio of 1:0 in the factor of one-time cooking were the optimal samples. This was because these samples’ acceptability was not significantly different from the comparison sample.